Towards organizational understanding of the notions of nexus and localization in humanitarian aid and development cooperation - García-Millán, Clara (2021)
The concepts of humanitarian-development nexus and localization have gained attention in global debates and international policies related to address the effectiveness and efficiency of crisis and conflict response. These two concepts have brought new terminologies and practices that could make a great impact in the work international aid providers do. However, development NGOs need to, first, learn these vocabularies, and second, turn them into strategies and practices in their particular organization. Therefore, the purpose of this research is to understand the organizational knowledge of Finn Church Aid on ‘nexus’ and ‘localization’ to support their organizational learning process and to contribute to the discussion of these concepts. The methods of data collection used in this research are semi-structured interviews and focus group discussions. Data was analysed through the method of qualitative content analysis. The results of this study reveal that FCA understands nexus as an alignment of efforts between humanitarian, development and peace actors in a mutually reinforcing manner. In addition, nexus is seen as a bottom-up, context-specific approach. On the other hand, the results indicate that FCA understands localization as local ownership, relationship quality, institutional capacity building and strengthening existing local capacities. Additional findings suggest that localization and nexus are directly interlinked in their conceptualization and implementation process.